4(12-u)/5=-4u+12

Simple and best practice solution for 4(12-u)/5=-4u+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(12-u)/5=-4u+12 equation:


u in (-oo:+oo)

(4*(12-u))/5 = 12-4*u // - 12-4*u

(4*(12-u))/5-(-4*u)-12 = 0

(4*(12-u))/5+4*u-12 = 0

(4*(12-u))/5+(4*5*u)/5+(-12*5)/5 = 0

4*(12-u)+4*5*u-12*5 = 0

16*u-60+48 = 0

16*u-12 = 0

(16*u-12)/5 = 0

(16*u-12)/5 = 0 // * 5

16*u-12 = 0

16*u-12 = 0 // + 12

16*u = 12 // : 16

u = 12/16

u = 3/4

u = 3/4

See similar equations:

| 24x+3=24 | | -8(3a-9)=0 | | y=-1/2*-2+2 | | (13x+45)+(19x+3)=180 | | -29+10y+7=3(4y-2)-4 | | 180-.14x=.29x | | 2(9x+7)-6x=3(4x+2)-9 | | 4x+7+2x=5 | | 2(1+x)/3=x+1 | | y=-1/2*-4+2 | | 180-.14=.29 | | 3x+7+x+8=39 | | 7/2x+1/2=27.5+9/2x | | -14=2(2x+3) | | 22x+7-27x=1-9 | | 16-x=4(4-3x) | | 6-5*3=y | | 3+4x=-3x+87 | | 7x+15-6x=-5-12 | | 6-5*2=y | | -18=3(y+1) | | -7x+7x=-x | | 71y=5(14y+29) | | x^2+3x+4=6 | | -7(-10+3)=x | | 6-5*1=y | | X^4-26x^2-160=0 | | 7/2x+1/2=271/2+9/2x | | 4(4a-1)=28 | | 32-5t=3t | | 7x+y=27 | | 14-.2(j-10)=.4(25+j) |

Equations solver categories